Caspase 8 - biomarker of extrinsic pathway of apoptosis in exogenic nitric oxide (NO) – induced death of rats’ hepatocytes - Pedrycz, Agnieszka; Zwierzyńska, Ewa; Siermontowski, Piotr; Orłowski, Marcin (Current Problems of Psychiatry, 2011)
The aim of present study was immunhistochemical evaluation of caspase 8 expression in L-arginine – substrate of nitric oxide (NO) induced apoptosis of rats’hepatocytes The rats used in this experiment were divided into 2 equal groups. Experimental: rats received per os L-arginine 40mg/kg body weight, every other day for 2 weeks and were decapitated after 3 weeks of the experiment. Control rats received per os 2ml of distilled water every other day for 2 weeks and were decapitated after 3 weeks of the experiment. Specimens of the liver taken after decapitation were examined in immunohistochemical way using standard three step method to detect immunolocalization of caspase 8. The results of immunohistochemical examinations were subjected to qualitative evaluation taking into account the intensity of colour reaction at the antigen-antibody site in rat liver examined in individual groups. The quantitative evaluation was using the Analysis-pro software. The surface area of cells with positive reaction (+) was calculated. The quantitative evaluation of caspase 8 expression showed that the area occupied by positive caspase 8 reaction in the rat liver of the experimental group (243,59 um2+/-262,43) was comparable to that in the control group (403,10 um2+/-215,91)(p=0,38). In the present study the dose of L-arginine was similar to that used in pregnant women treated for gestosis. The study shows that L-arginine as a donor of exogenous nitric oxide did not have an apoptotic effect leading by extrinsic pathway on the hepatocytes of the rats.